Refinance Instruments : Lessons From their Use in Some Industrialized Countries - Laurens, Bernard (IMF Working Papers; Working Paper ;, 1994)
Many central banks around the world are gradually shifting from a system of direct controls towards the implementation of monetary policy through market-oriented instruments, including refinance facilities. This paper reviews the use of refinance instruments in a sample of industrialized countries, and discusses how central banks use them to influence short-term interest rates and to manage banks' reserves. Some lessons are suggested for their implementation in developing countries or economies in transition.